IMPLEMENTASI PRINSIP KEADILAN DALAM HUKUM PERJANJIAN SYARI’AH - Zaenudin Mansyur (Asy-Syari'ah, 2020)
Abstract: This paper will examine the implementation of the eighth values which appear to be unclear in transactions and sharia agreements, especially in the aspects of the pre-process agreement, process, and post-process. Meanwhile, the use of descriptive analysis method with the provision of the theory of justice can reveal the extent to which the value of justice can be implemented for the parties in the study. Thus, procedural justice is implemented in determining the subject of the agreement at least tamyiz in the pre-process, namely the parties are able to take responsibility for their own agreements which are not the responsibility of others even though the parents themselves. While in the stage of the justice process it is also often part of what can be implemented in an agreement. For example implementing proportional justice in qabul consent. Because the purpose of the stipulation is to know the extent of the readiness and willingness of each party in the agreement. Whereas in the post-process process, the value of justice can also be implemented in the form of the transfer or implementation of rights and obligations for each party. Where the value of justice in this condition is al-mizan or the similarity of scales in terms of quality and quantity.